The Analysis Study of Diagnostic Imaging Performance and Accuracy of Tuberculosis: A Systematic Review - Shani Abidi; Handri Andika (The International Journal of Medical Science and Health Research, 2025)
Background: Tuberculosis (TB) remains a major global health challenge, with its variable clinical presentations often complicating timely and accurate diagnosis. Diagnostic imaging modalities such as chest X-ray, computed tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography/computed tomography (PET/CT) provide varying degrees of sensitivity and specificity depending on disease location and progression. However, diagnostic accuracy may be influenced by interobserver variability, regional disease prevalence, and coexisting conditions. This systematic review aims to critically evaluate and compare the diagnostic performance and accuracy of various imaging techniques in TB to support evidence-based clinical decision-making. Methods: This review adhered strictly to the PRISMA 2020 guidelines, incorporating only full-text, peer-reviewed articles published in English between 2015 and 2025. To ensure the credibility and traceability of sources, editorial pieces and review articles lacking a Digital Object Identifier (DOI) were excluded. A comprehensive search strategy was implemented across three major academic databases—ScienceDirect, PubMed, and SAGE Publications—to identify studies directly relevant to the research objectives. Result: The initial database search yielded over 100 potentially relevant studies. Through a structured three-phase screening and selection process, eight studies fulfilled the predefined inclusion criteria and were selected for detailed analysis. These studies were rigorously appraised for methodological quality and relevance, ensuring that the final synthesis was based on robust and high-quality evidence. The findings provide critical insight into the strengths and limitations of each imaging modality in the context of TB diagnosis. Conclusion: Diagnostic imaging is a cornerstone in the evaluation of tuberculosis, with each modality offering distinct advantages depending on the clinical scenario. CT thorax demonstrates the highest accuracy for detecting pulmonary TB, while MRI is superior for assessing extrapulmonary manifestations, particularly in the central nervous system and spine. Ultrasonography (USG) serves as a valuable adjunct in evaluating abdominal and pleural involvement. A tailored, context-specific imaging strategy is essential to enhance diagnostic precision and optimize patient management.